NILAI-NILAI NASIONALISME PADA PUISI DONGENG PAHLAWAN KARYA WS. RENDRA - Sunarti Sunarti; Maulana Yusup; Heri Isnaini (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This article discusses the values of nationalism in W.S. Rendra's poem "Heroes' Tale." The poem is found in the Stanzas and Blues. The poem "Fairy Tales of Heroes" is assumed to have values of nationalism and heroic values. The focus of this research is based on two problems. 1) how the values of nationalism are built on the poem "Tale of Heroes" by W.S. Rendra; and 2) how the values of nationalism build character values that can be utilized in the learning process. Both issues will be examined based on the theory of symbols covered in the dictions in poetry. The method used is qualitative method by making poetry as an object and research data. The results of this study showed that the values of nationalism in the poem "Dongeng Pahlawan" by W.S. Rendra were built on conventional symbols. The symbols are contained in the dictions used.In addition, character values appear in line with the found values of nationalism. Thus, W.S. Rendra's poem "Hero's Tale" has important values in building the character of nationalism that is indispensable in building our nation and country.Â